2015
DOI: 10.1038/ncomms7326
|View full text |Cite
|
Sign up to set email alerts
|

Long-range epigenetic regulation is conferred by genetic variation located at thousands of independent loci

Abstract: The interplay between genetic and epigenetic variation is only partially understood. One form of epigenetic variation is methylation at CpG sites, which can be measured as methylation quantitative trait loci (meQTL). Here we report that in a panel of lymphocytes from 1,748 individuals, methylation levels at 1,919 CpG sites are correlated with at least one distal (trans) single-nucleotide polymorphism (SNP) (P<3.2 × 10−13; FDR<5%). These trans-meQTLs include 1,657 SNP–CpG pairs from different chromosomes and 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
113
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(132 citation statements)
references
References 65 publications
17
113
0
2
Order By: Relevance
“…8 A study by Lemire et al demonstrated that there is extensive long-range regulation of CpG methylation associated with genetic variation. 26 The fact that CpG sites associated with a SNP were not excluded in the present study may affect heritability analysis and explain why we obtain 1,186 significant probes that give an estimated maximal heritability of 100%. To verify that, we conducted further analysis to investigate SNPs position in these probe locations using the 1,000 Genomes Project Phase 1 Version 3.…”
Section: Discussionmentioning
confidence: 83%
“…8 A study by Lemire et al demonstrated that there is extensive long-range regulation of CpG methylation associated with genetic variation. 26 The fact that CpG sites associated with a SNP were not excluded in the present study may affect heritability analysis and explain why we obtain 1,186 significant probes that give an estimated maximal heritability of 100%. To verify that, we conducted further analysis to investigate SNPs position in these probe locations using the 1,000 Genomes Project Phase 1 Version 3.…”
Section: Discussionmentioning
confidence: 83%
“…Another study quantified DNA methylation levels in lymphocytes of several hundred individuals with a chip assaying 450,000 CpG sites. This approach revealed both local ( cis ) and distant ( trans ) methylation QTLs that were in high LD to autoimmune disease variants 154 . This colocalization does not necessarily mean that the actual disease variant is affecting DNA methylation.…”
Section: Quantifying Immune-related Phenotypesmentioning
confidence: 99%
“…There have been numerous reports of SNPs affecting the hypermethylation of proximal and trans-gene CpG islands, [2][3][4][5][6] Table 3. Allele frequencies for the non-hg19 SNP alleles that occur most frequently in the indicated data sets and that create or eliminate CpG's.…”
Section: Discussionmentioning
confidence: 99%